2012
DOI: 10.1097/mao.0b013e318254fbc2
|View full text |Cite
|
Sign up to set email alerts
|

Is Cartilage Tympanoplasty More Effective Than Fascia Tympanoplasty? A Systematic Review

Abstract: Tympanoplasty using cartilage with or without perichondrium has better morphological outcome than tympanoplasty using temporalis fascia. However, there was no statistically significant difference in hearing outcomes between the 2 grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
100
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(113 citation statements)
references
References 13 publications
6
100
1
6
Order By: Relevance
“…Yet, many studies have shown that there is no difference in the use of cartilage or fascia in morphological or hearing aspects [3,5,6,23] . Even studies reporting better hearing results in tympanoplasty with cartilage are present [22] .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Yet, many studies have shown that there is no difference in the use of cartilage or fascia in morphological or hearing aspects [3,5,6,23] . Even studies reporting better hearing results in tympanoplasty with cartilage are present [22] .…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the use of cartilage in tympanoplasty has been known for many years; however, because of the doubt of the negative effect on sound conduction, it is not used [3,4,6] . Yet, many studies have shown that there is no difference in the use of cartilage or fascia in morphological or hearing aspects [3,5,6,23] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations